Relative biological effectiveness of single and split helium ion doses in the rat spinal cord increases strongly with linear energy transfer - Hintz, Lisa; Glowa, Christin; Saager, Maria; Euler-Lange, Rosemarie; Peschke, Peter; Brons, Stephan; Grün, Rebecca; Scholz, Michael; Mein, Stewart; Mairani, Andrea; Debus, Jürgen; Karger, Christian (Radiotherapy and oncology, 2022)
Background and purpose - Determination of the relative biological effectiveness (RBE) of helium ions as a function of linear energy transfer (LET) for single and split doses using the rat cervical spinal cord as model system for late-responding normal tissue. - Material and methods - The rat cervical spinal cord was irradiated at four different positions within a 6 cm spread-out Bragg-peak (SOBP) (LET 2.9, 9.4, 14.4 and 20.7 keV/µm) using increasing levels of single or split doses of helium ions. Dose-response curves were determined and based on TD50-values (dose at 50% effect probability using paresis II as endpoint), RBE-values were derived for the endpoint of radiation-induced myelopathy. - Results - With increasing LET, RBE-values increased from 1.13 ± 0.04 to 1.42 ± 0.05 (single dose) and 1.12 ± 0.03 to 1.50 ± 0.04 (split doses) as TD50-values decreased from 21.7 ± 0.3 Gy to 17.3 ± 0.3 Gy (single dose) and 30.6 ± 0.3 Gy to 22.9 ± 0.3 Gy (split doses), respectively. RBE-models (LEM I and IV, mMKM) deviated differently for single and split doses but described the RBE variation in the high-LET region sufficiently accurate. - Conclusion - This study established the LET-dependence of the RBE for late effects in the central nervous system after single and split doses of helium ions. The results extend the existing database for protons and carbon ions and allow systematic testing of RBE-models. While the RBE-values of helium were generally lower than for carbon ions, the increase at the distal edge of the Bragg-peak was larger than for protons, making detailed RBE-modeling necessary.